Tingkat Literasi Media Baru Kalangan Remaja Dalam Penggunaan Media Sosial (Studi Kasus di Nagari Lareh Nan Panjang, Kecamatan VII Koto Sungai Sarik, Kabupaten Padang Pariaman, Provinsi Sumatera Barat) - Fauziah, Fauziah; Nelisa, Malta (Scinary, 2024)
This research aims to describe the level of new media literacy of adolescents in using social media at the stages of functional consuming, critical consuming, functional prosuming, and critical prosuming. This research uses quantitative research with descriptive methods. The population in the study amounted to 365 people. Samples were taken as many as 79 respondents, namely adolescents in Nagari Lareh Nan Panjang, VII Koto Sungai Sarik District, Padang Pariaman Regency, West Sumatra Province. The sampling technique used was purposive sampling. Data was collected using a questionnaire through google form with a likert scale. The results of this study indicate that: the level of new media literacy among adolescents in the use of social media scored 2.97, which is in the interval 2.50 - 3.24, which is categorized as high. (1) in functional consuming, it scored 3.11 which is in the interval 2.50 - 3.24, so it can be concluded that the adolescents of Nagari Lareh Nan Panjang have a high ability to access and understand the media content delivered; (2) in critical consuming, it has an average score of 2.95 which is in the interval 2.50 - 3.24, so it can be concluded that the adolescents of Nagari Lareh Nan Panjang have a high ability to assess and analyze media content in depth; (3) in functional prosuming, it scored 2.91 which is in the interval 2.50 - 3.24, so it can be concluded that the adolescents of Nagari Lareh Nan Panjang have a high ability to create media content and actively participate in new media spaces; (4) in critical prosuming, it has a score of 2.92 which is in the interval 2.50 - 3.24, so it can be concluded that the adolescents of Nagari Lareh Nan Panjang have a high ability to actively and critically participate in social media.